Positive Sentiment and the Donation Amount: Social Norms in Crowdfunding Donations During the COVID-19 Pandemic - Peng, Yan; Li, Yuxin; Wei, Lijia (Frontiers in Psychology, 2022)
Public welfare fundraising has been used to collect donations for medical supplies and has played an important role in the fight against the COVID-19 pandemic. This paper studies online crowdfunding donations from the Alumni Association of Wuhan University to North American alumni; donation data are used to investigate how individuals’ donation behavior is affected by the previous donation amount and information provided by the fundraising platform. First, our results show that one’s donation amount is positively affected by the previous donation amount. Second, the donor’s positive sentiment in the message that he or she leaves, as measured by either natural language processing or a manual rating, can affect the subsequent anonymity and messages but not the subsequent donation amount. Third, anonymous donations are much smaller than nonanonymous donations.